Reinforced concrete with FRP bars mechanics and design - Nanni, Antonio (CRC Press/Taylor & Francis Group, 2014)
This book is mainly intended for practitioners and focuses on the fundamentals of performance and design of concrete members with FRP reinforcement and reinforcement detailing. Graduate students and researchers can use it as a valuable resource